IMPACT INTERGOVERNMENTAL TRANSFER ON FOREST CONSERVATION IN INDONESIA - Wiyekti, Ndari; Riatu Mariatul Qibthiyyah (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2021)
This study discusses the impact of Intergovernmental Fiscal Transfers (IFT) on forest conservation in Indonesia from 459 districts/cities during the period 2008-2016 using a panel model in the form of Fixed Effect and Spatial Autoregressive (SAR) Fixed Effect. The analysis distinguished by the district/city level and provincial level. The results show the influence of IFT on the expansion of forest conservation areas in Indonesia. For the district/city level, IFT has a positive relationship both in the form of balance funds and in the form of coordination funds. In particular, the area of forest conservation in Indonesia increased when the Special Allocation Fund (DAK) and Revenue Sharing Fund (DBH) increased. While the Coordination Fund, only the Assistance Task Fund (TP) positively has a significant effect. The impact of the adjacent area or neighborhood effect is empirically affecting the expansion of forest conservation areas in Indonesia. The impact is seen in positive spatial coefficients. So it can be concluded, for the provision of public goods such as forest conservation areas causes a mimicry effect. Public goods that have a positive spillover will rise a mimicry, participation in the provision of adjacent areas. Forest management involving multi-level governance makes the provision of conservation areas more effective and efficient. Central and Local Governments can coordinate to expand conservation areas to gain benefits for the future. Keywords: Intergovernmental Transfer, Public Goods, Forest Conservation.